Management change in East Germany unification and transformation - Edwards, Vincent; Lawrence, Peter (Routledge, 1994)
When Germany reunified, the nature of business and styles of management in East Germany were set to change; but how were they to adapt and what has really happened? Taking a long-term look at the way business was done before and after the collapse of the Berlin Wall, this book offers an important analysis of the changes in management practice and organisational culture in East Germany. With comparisons of management styles throughout Europe, the study assesses the varying degrees of success achieved by employing these strategies within the transformation of East Germany. The study encompasses discussions of the structure of companies and the new management culture, as well as of labour and human resource problems, privatisation, entrepreneurship and finance, placing it all within the context of change in everyday life. It concludes with an exploration into who wins and who loses in the New Germany.
Keywords: Ondernemingsklimaat; Organisatieverandering; Privatisering; Corporate culture -- Germany (East); Organizational change -- Germany (East); Post-communism -- Germany (East); Privatization -- Germany (East); Strategic planning -- Germany (East); Wirtschaftsreform; Wirtschaftssystem; Restrukturierung; Volkseigener Betrieb; Transformation; Privatisierung; Management; Deutschland -- Östliche Länder